Efektivitas Aplikasi Quizlet untuk Penguasaan Kosakata Siswa Kelas X Lintas Minat 1 Bahasa Mandarin - Hersa, Sisca Tri; Kurniawan, Deddy; Mardasari, Octi Rjeky (Universitas Negeri Malang, 2024)
This study investigates the effectiveness of Quizlet, an online learning tool, in improving Chinese vocabulary mastery among high school students. Quizlet, designed as a flashcard game, offers an interactive approach to vocabulary learning, particularly in foreign languages, aiming to make the process both enjoyable and effective in capturing students' interest. The research aims to assess students' Chinese vocabulary mastery levels before and after using Quizlet and evaluate the effectiveness of this educational media. Employing a pre-experimental method with a one-group pretest-posttest design, the study involves 22 students from class X Lintas Minat 1 Bahasa Mandarin at State High School 1 Batu as the sample population. A pretest was administered to assess baseline proficiency, followed by treatment using Quizlet, and a posttest to evaluate improvement. Data analysis utilized the n gain formula. Findings indicate a significant improvement in Chinese vocabulary mastery, specifically in the topic of measure words or 量词 [liàngcí]. The pretest score averaged 74.90, while the posttest score rose to 90.86, reflecting a substantial increase of 15.96 points after Quizlet implementation. The study concludes that Quizlet is an effective tool for enhancing Chinese vocabulary learning among students in class X Lintas Minat 1 Bahasa Mandarin at State High School 1 Batu, highlighting its potential as a valuable resource in language education.